Tideborn - Chan, Eliza (Chan, Eliza. Drowned world, 2025)
"A tsunami and a dragon's wish have wrought changes upon the city of Tiankawi that have never been seen before. But shared experiences have not healed the rift between the city's fathomfolk and human citizens, and scars from years of oppression still remain. Mira, a half-siren and activist, fights politicians and her own people to rebuild her city and to uncover a deadly conspiracy. And Nami, the dragon princess, undertakes a daring ocean voyage alongside friend and foe in order to convince a mythical Titan not to destroy Tiankawi for its crime"--